2011
DOI: 10.1073/pnas.1100633108
|View full text |Cite
|
Sign up to set email alerts
|

Anuran radiations and the evolution of tadpole morphospace

Abstract: Anurans (frogs and toads) are unique among land vertebrates in possessing a free-living larval stage that, parallel to adult frogs, diversified into an impressive range of ecomorphs. The tempo and mode at which tadpole morphology evolved through anuran history as well as its relationship to lineage diversification remain elusive. We used a molecular phylogenetic framework to examine patterns of morphological evolution in tadpoles in light of observed episodes of accelerated lineage diversification. Our reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 60 publications
8
81
1
2
Order By: Relevance
“…We documented patterns in the class I evolutionary trees that indicated trans-species polymorphism had occurred (some allelic lineages on the tree contained sequences from multiple species). The genus Lithobates may be as old as 36-39 million years, while the divergence between A. callidryas and E. prosoblepon dates back to 68-91 million years ago (Roelants et al, 2011). In comparison, the oldest DRB1 allelic lineages in primates are estimated to be B55 million years old (Klein et al, 1998) and allelic lineages are shared between Ruminanta genera that diverged over 30 million years ago (Ballingall et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We documented patterns in the class I evolutionary trees that indicated trans-species polymorphism had occurred (some allelic lineages on the tree contained sequences from multiple species). The genus Lithobates may be as old as 36-39 million years, while the divergence between A. callidryas and E. prosoblepon dates back to 68-91 million years ago (Roelants et al, 2011). In comparison, the oldest DRB1 allelic lineages in primates are estimated to be B55 million years old (Klein et al, 1998) and allelic lineages are shared between Ruminanta genera that diverged over 30 million years ago (Ballingall et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tadpoles of Lepidobatrachus are suctorial (O'Reilly et al 2002) and able to swallow large prey. Roelants et al (2011) found several anuran clades, whose tadpoles are classified as Orton's morphotype IV (Anomocoela, Nobleobatrachia, Natatanura, and Afrobatrachia) occupy contiguous or even overlapping regions in morphospace. Together, these clades are estimated to contain over 80% of modern anuran species, implying that the majority of extant tadpoles are concentrated in a relatively small part of morphospace.…”
Section: Heterocrhony In Ceratophryinesmentioning
confidence: 99%
“…The recent paper by Roelants et al (2011) analyzed the anuran radiations and the evolution of tadpole morphospace and found the slowdown in the morphospace expansion was caused not only by a drop in evolutionary rate after the basal anuran radiation but also by an overall increase in homoplasy in the characters that did evolve during later radiations that may have enhanced tadpole diversity by creating unique combinations of homoplastic traits, but the lack of innovative character changes prevented the exploration of fundamental regions in morphospace.…”
Section: Introductionmentioning
confidence: 98%
“…Early developmental stages of the African clawed frog [X. laevis (Daudin 1802) Pipidae] are commonly used in toxicological studies as surrogates for other aquatic organisms, including amphibians, because of their high sensitivity to pesticides and their availability for use in the laboratory (ASTM 1998;Bantle et al 1998Bantle et al , 1999OECD 2009;Wagner et al 2015). Xenopus larvae [larval type I (pipid type)] are understood as derived within anurans and the larval types IV and III as the phylogenetically basic morphotypes (Roelants et al 2011). This is in good agreement with a lot of their biological features.…”
mentioning
confidence: 99%